Pattern of methane levels with lactulose breath testing; can we shorten the test duration?. Issue 7 (17th June 2021) - Shaker, Anisa; Peng, Billy; Soffer, Edy
Abstract: Background and Aim: Methane levels in methane‐positive lactulose breath tests are frequently elevated at time zero. We hypothesized that baseline methane level is sufficient to detect excessive methane production and thereby avoid extended testing. Our aim was to determine if baseline methane levels were sufficient to identify methane‐positive individuals as defined by current guidelines. Methods: A retrospective study of lactulose breath tests was conducted at an open access motility lab. A methane‐positive study was defined as a methane level ≥10 ppm at any time. Small intestinal bacterial overgrowth (SIBO) was defined as a ≥20 ppm rise in hydrogen from baseline by 90 min. Dual‐positive SIBO and methane studies were identified. Demographics, symptoms, and indications were recorded. Results: Of 745 tests, 33.1%, 15.0%, and 3.1% were SIBO, methane, and dual‐positive, respectively. Precisely 96.4% of methane‐positive studies had methane levels ≥10 ppm within 90 min and 75.9% had levels ≥10 ppm at time 0. An additional elevation of ≥20 ppm over baseline within 90 min was observed in 32.1%. Of 22 methane‐positive patients with constipation, methane levels were ≥10 ppm at baseline in 81.8% and were ≥10 ppm within 90 min in all cases. Conclusions: Nearly 25% of methane‐positive studies were not identified by a fasting methane level, but 96% were identified within 90 min. Most methane‐positive studies did not have a rise of 20 ppm above baseline. Our findings suggest the lactulose breath test for hydrogen and methane can be complete at 90 min. Abstract : Nearly 25% of methane‐positive studies were not identified by a fasting methane level, but 96% were identified within 90 min. Most methane‐positive studies did not have a rise of 20 ppm above baseline. Our findings suggest the lactulose breath test for hydrogen and methane can be complete at 90 min.